Self-disinfecting PDMS surfaces with high quaternary ammonium functionality by direct surface photoinitiated polymerization of vinylbenzyl dimethylbutylammonium chloride. (5th June 2021) - Lou, Yuzhen; Schapman, Damien; Mercier, Dimitri; Alexandre, Stéphane; Burel, Fabrice; Thebault, Pascal; Kébir, Nasreddine
Graphical abstract: Highlights: Preparation of PDMS surfaces with high quaternary ammonium density by a 'grafting from' process. Use of a direct surface photo-initiated polymerization of vinylbenzyl dimethylbutyl ammonium chloride. Obtention of surface charge densities above 10 17 charge/cm 2 . The obtained surfaces kill efficiently the bacteria on the surface and in suspension. Abstract: Vinylbenzyl dimethylbutylammonium chloride was successfully grafted and photo-polymerized from a PDMS surface, in presence of benzophenone. The obtained surface exhibited quaternary ammonium density above 10 17 charge/cm 2 and very high hydrophilicity compared to ungrafted surfaces. Bacterial enumeration and fluorescence microscopy revealed an efficient contact killing of this surface against Escherichia coli, Staphylococcus aureus and Staphylococcus epidermidis .